Effects of Biophotonic Treatment on Glycemic, Metabolic, and Hematologic Parameters - Tulp, Orien L.; Rizvi, Syed A. A.; Einstein, George P. (British Journal of Healthcare and Medical Research, 2024)
The wide-ranging effects of healthful vs. damaging consequences of UV irradiation on key physiologic parameters linked to carbohydrate metabolism are reviewed in this paper. The effects are largely dependent on the wavelengths encountered, the absolute intensity and duration of the exposure, the tissues exposed, and whether the UV effects were delivered via in vivo, as an extracorporeal exposure of intact tissues or in vitro from freshly obtained heparinized aliquots of whole blood. While damaging effects of high UV intensity may include irreversible irradiation damage to molecular components, administration of controlled low dosages and controlled wavelengths of UV irradiation delivered via a conventional biophotonic apparatus can deliver beneficial effects on blood oxygenation, tissue repair, immune responses, glycemic responses, and glycated hemoglobin (HbA1c) concentrations. HbA1c percentage in whole blood is a major diagnostic marker for the effectiveness of diabetes management. In studies with diabetic mouse models, GLUT4, Oral Glucose Tolerance, Insulin response to a glucose challenge, ATP content, and glycogen synthesis in skeletal muscle were found to be significantly improved following photonic treatments. In vivo Studies reviewed demonstrated increases in blood oxygenation and corresponding decreases in HbA1c concentrations following nominal biophotonic treatment. These observations indicate that the application of biophotonic therapy extends beyond its more commonly applied applications for the treatment and control of infectious illnesses and anti-aging therapeutics and may also include important potential beneficial effects in obesity and insulin resistant conditions typical of type 2 diabetes mellitus.